Polyamines mediate the inhibitory effect of drought stress on nitrogen reallocation and utilization to regulate grain number in wheat - Li, Juan; Li, Qi; Nian, GUO; Xian, Qinglin; Lan, Bing; Nangia, Vinay; Mo, Fei; Liu, Yang (Oxford University Press (OUP): Policy F - Oxford Open Option D, 2024)
Drought stress poses a serious threat to grain formation in wheat. Nitrogen (N) plays crucial roles in plant organ development; however, the physiological mechanisms by which drought stress affects plant N availability and mediates the formation of grains in spikes of winter wheat are still unclear. In this study, we determined that pre-reproductive drought stress significantly reduced the number of fertile florets and the number of grains formed. Transcriptome analysis demonstrated that this was related to N metabolism, and in particular, the metabolism pathways of arginine (the main precursor for synthesis of polyamine) and proline. Continuous drought stress restricted plant N accumulation and reallocation rates, and plants preferentially allocated more N to spike development. As the activities of amino acid biosynthesis enzymes and catabolic enzymes were inhibited, more free amino acids accumulated in young spikes. The expression of polyamine synthase genes was down-regulated under drought stress, whilst expression of genes encoding catabolic enzymes was enhanced, resulting in reductions in endogenous spermidine and putrescine. Treatment with exogenous spermidine optimized N allocation in young spikes and leaves, which greatly alleviated the drought-induced reduction in the number of grains per spike. Overall, our results show that pre-reproductive drought stress affects wheat grain numbers by regulating N redistribution and polyamine metabolism.